PROTECTIVE EFFECT OF Pterocarpus mildbraedii HARMS EXTRACT ON PROPANIL-INDUCED HEPATOTOXICITY AND ALTERATIONS IN APOPTOTIC-RELATED PROTEINS IN WISTAR RATS (2017)
One of the probable causes of liver diseases is exposure to environmental chemicals. Agrochemicals containing propanil are known to induce hepatic toxicity. Pterocarpus mildbraedii leaf is used in traditional medicine to treat various disorders without scientific justification. This study was designed to investigate the protective role of extract of Pterocarpus mildbraedii against propanil-induced hepatotoxicity in rats. Pterocarpus mildbraedii leaves, purchased from Oyingbo market, Lagos State, were authenticated at the University of Lagos Herbarium (LUT/5913). Powdered leaf was extracted in soxhlet, using dichloromethane:methanol (1:1), to yield crude extract of Pterocarpus mildbraedii (PME). Sixty-four male Wistar rats (130-160 g), comprising of eight groups (n=8) were used for these experiments. Rats were treated orally with normal saline (control), PME (100 mg/kg), PME (200 mg/kg), PME (400 mg/kg), propanil (200 mg/kg), PME (100 mg/kg) + propanil (200 mg/kg), PME (200 mg/kg) + propanil (200 mg/kg) and PME (400 mg/kg) + propanil (200 mg/kg) for seven consecutive days. Hepatic tissues and serum were assayed for markers of hepatic damage, oxidative stress, inflammation, and apoptosis. Aspartate aminotransferase (AST), lactate dehydrogenase (LDH), bilirubin (BIL), superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH), malondialdehyde (MDA), myeloperoxidase (MPO) and nitric oxide (NO) were assayed by spectrophotometry. Inducible Nitric Oxide Synthase (iNOS), Cyclooxygenase-2 (COX-2), Nuclear factor kappa B (NF-κB), Caspase 3, Caspase 9, Bax, Bcl-2 expressions were measured using immunohistochemistry. Tumour suppressor p53, Bcl-2 antagonist of cell death (Bad), NF-κB, inhibitor of total nuclear factor-kappa B α (IκB α), stress activated protein kinase/ C Jun NH2-terminal kinase (SAPK/JNK), p38 mitogen-activated protein kinase (p38) and signal transducer and activator of transcription 3 (STAT 3) were assessed by ELISA. Histopathology of liver was determined by microscopy and apoptosis by TUNEL assay. Data were analysed using ANOVA at α0.05. The yield of PME was 41.9%. Administration of propanil significantly increased AST (132.10±6.32 U/L), LDH (85.70±6.60 U/L), BIL (1.15±0.16 mg/dL), SOD (0.97±0.05 U/mg protein), MDA (1.03±0.08 µgMDA/mg protein), MPO (4.98±0.12 µmol/min/mg protein) and NO (0.38 µmol/mg protein) relative to control (115.90±8.65, 32.84±9.39, 1.15±0.16, 0.38± 0.01, 0.40±0.11, 2.47±0.10 and 0.19± 0.05, respectively). Pre-treatment of propanil-exposed rats with PME (200 mg/kg) significantly decreased LDH (83%), BIL (50%), SOD (50.5%), MDA (33.1%), MPO (63.3%) and NO (59.5%). Further, propanil administration decreased the levels of GSH (2.98±0.24 µg/mg protein) and CAT (52.7±0.24 µmol H202 consumed/min/g tissue) when compared with the controls (2.04±0.09 and 51.00±0.51). However, intervention with PME restored these serum biochemical indices and antioxidant parameters back to normal values. Expressions of iNOS, COX-2, NFκB, Caspase 3, Caspase 9 and Bax were higher in the propanil group relative to control. Levels of signaling mediators p38 (81.28±7.70), STAT 3 (88.80±4.40) and NF-κB (72.76± 5.30) were lower, while SAPK (125.39±9.30), IκB α (115.83±5.60) and Bad (112.48±4.70) were higher in propanil-treated rats relative to control value set at 100. TUNEL-positive nuclei and severe periportal fibrosis were observed in tissues following propanil exposure. However, pre-treatment with PME significantly attenuated the observed propanil-induced inflammation and apoptosis. Pterocarpus mildbraedii extract protected against propanil-induced hepatotoxicity via mechanisms that involved its antioxidant, anti-inflammatory and anti-apoptotic properties.